THE STUDY OF ANTIFUNGAL ACTIVITY FROM INDIGENOUS PLANTS FROM INDONESIA: AN IN VITRO STUDY - Sukandar, Elin Yulinah; Fidrianny, Irda; Susanto, Eriwan; Safitri, Dewi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aimed to analyze new agents from extracted Indo esiaherbs possessing antifungal activity with better safety profile againstCandida albicans, Microsporum gypseum, and Trichophyton mentagrophytes. Methods: The screening of 11 herbs was performed to determine the highest antifungal activity. Minimum inhibitory concentration and minimum fungicidal concentration of selected extracts, rosemary (Rosmarinus officinalis) leaves, java turmeric (Curcuma xanthorrhiza) rhizome, and ginger (Zingiber officinale) rhizome were determined using microdilution and agar diffusion methods. Extracts were then combined to evaluate further activities. Selected extracts were fractionated using liquid-liquid extraction, analyzed by thin-layer chromatography-direct (TLC) bioautography. Results: Ethanolic extract of rosemary (R. officinalis) leaves, java turmeric (C. xanthorrihza) rhizome, and ginger (Z. officinalis) rhizome in combination showed the highest activity and synergistic interaction against Trichophyton mentagrophytes. There were several components from fractions that actively inhibited corresponding fungi according to TLC bioautography method. Conclusion: Ethanolic extracts of rosemary, java turmeric, and ginger had the highest antifungal potency, both as extract and in combination comparable to ketoconazole as reference drug. These selected extracts are potential to be used as new antifungal agents. Keywords: Antifungal, Rosemary, Ginger, Java turmeric, In situ, Bioautography thin-layer chromatography-direct.